THE NEED FOR PROBLEM SOLVING SKILLS IN DANIEL DEFOE'S ROBINSON CRUSOE: A SOCIOLOGICAL APPROACH - KHUSNAIDI , SABIQ (2007)
The major problem of this study is how problem solving skills are reflected in Daniel Defoe's Robinson Crusoe. The objective of this study is to analyze the novel based on the structural elements and to analyze the novel based on the sociological approach. This study belongs to qualitative methods. In this method, they are two data types of data source, namely primary and secondary data source. The primary data is the novel itself and secondary data is the theory of sociological approach, which is proposed by Alan Swingewood and Diana Laurenson, and other books that are related to the research. The study uses library research of descriptive analysis. The outcome of this study shows that problem solving skills are resulted from social conflicts in the society among the characters. The structural elements of the novel that consist of character and characterization, setting, plot, point of view, style and theme also influence the major character in facing the problem using problem solving skills. Besides that, the sociological perspective become the main aspect in examine the need for problem solving skills in the novel that is suitable with the society in England at late seventeenth and early eighteenth century.